Risk factors for pulmonary embolism in patients with paralysis and deep venous thrombosis - Keller, Karsten; Wöllner, Jens; Schmitt, Volker H.; Ostad, Mir A.; Sagoschen, Ingo; Münzel, Thomas; Espinola-Klein, Christine; Hobohm, Lukas (Journal of Clinical Medicine, 2021)
Background. Venous thromboembolism is a frequent complication and an important cause of death in patients with paralysis. We aimed to investigate predictors of pulmonary embolism (PE) and the impact of PE on the survival of patients with paralysis in comparison to those with deep venous thrombosis or thrombophlebitis (DVT). Methods: Patients were selected by screening the German nationwide inpatient sample (2005-2017) for paralysis, and were stratified for venous thromboembolism (VTE) and the VTE-sub-entity PE (ICD-code I26). Impact of PE on mortality and predictors for PE were analyzed. Results: Overall, 7,873,769 hospitalizations of patients with paralysis were recorded in Germany 2005-2017, of whom 1.6% had VTE and 7.0% died. While annual hospitalizations increased (2005: 520,357 to 2017: 663,998) (β 12,421 (95% CI 10,807 to 14,034), p < 0.001), in-hospital mortality decreased from 7.5% to 6.7% (β −0.08% (95% CI −0.10% to −0.06%), p < 0.001). When focusing on 82,558 patients with paralysis hospitalized due to VTE (51.8% females; 58.3% aged ≥ 70 years) in 2005-2017, in-hospital mortality was significantly higher in patients with paralysis and PE than in those with DVT only (23.8% vs. 6.3%, p < 0.001). Cancer (OR 2.18 (95% CI 2.09-2.27), p < 0.001), heart failure (OR 1.83 (95% CI 1.76-1.91), p < 0.001), COPD (OR 1.63 (95% CI 1.53-1.72), p < 0.001) and obesity (OR 1.42 (95% CI 1.35-1.50), p < 0.001) were associated with PE. PE (OR 4.28 (95% CI 4.07-4.50), p < 0.001) was a strong predictor of in-hospital mortality. Conclusions: In Germany, annual hospitalizations of patients with paralysis increased in 2005-2017, in whom VTE and especially PE substantially affected in-hospital mortality. Cancer, heart failure, COPD, obesity and acute paraplegia were risk factors of PE.
Gesehen am 05.01.2022